Methane oxidation dynamics in a stratified lake: Insights revealed from a mass balance and carbon stable isotopes. Issue 10 (30th July 2022) - Langenegger, Timon; Vachon, Dominic; Donis, Daphne; McGinnis, Daniel F.
Abstract: Methane oxidation in lakes removes a large portion of methane (CH4 ). To date, methane oxidation estimates in lakes have often been derived at low spatial resolution in the water column, preventing understanding of the links to the physicochemical gradients in the stratified regions. We applied a mass balance approach with measured dissolved CH4 and sediment CH4 fluxes to derive high‐resolution depth profiles of specific CH4 oxidation rates ( k ox ) in the water column during the stratified period of a small eutrophic lake (Soppensee, Switzerland). Estimated k ox ranged from 0 to 1 d −1 and the k ox profiles agreed well with previous studies, and were also in agreement with rates from concurrent in situ oxidation experiments. A sensitivity analysis revealed that sediment CH4 flux is the largest source of uncertainty when deriving k ox . Although previous studies have estimated methane oxidation based on δ 13 CCH4, we showed with numerical modeling that δ 13 CCH4 measurements could not be used to resolve the relative contributions of methane oxidation and sediment fluxes to the water column CH4 balance. Exploration of alternative approaches to derive methane oxidation is needed to reveal potentially unknown or misunderstood drivers of methane oxidation in lakes. The presented mass balance approach has the potential to calculate methane oxidation at high vertical resolution and enhance the spatial limitations of established incubation methods. As methane oxidation is responsible for removing most of the produced methane in lakes, it is as important to accurately resolve the key drivers to predict responses to future climate scenarios.